2023
DOI: 10.1108/agjsr-09-2022-0168
|View full text |Cite
|
Sign up to set email alerts
|

Halal standards’ implementation in Palestinian food sector: its drivers and impact on performance

Abstract: PurposeThe purpose of this paper is to study the correlational and effect relationship between Halal standards and the performance of Halal-certified Palestinian Food Companies.Design/methodology/approachQuantitative method was used, using a questionnaire survey of 40 Halal-certified Palestinian organizations out of a total of 47 certified organizations, the analysis was done using the partial least squares structural equation modeling (PLS-SEM) and the literature review was conducted using a well-known system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…It utilizes the Meta-Analysis approach, which employs a more transparent, scientific and replicable process. In other words, it is a detailed technology that aims to minimize bias through exhaustive literature searches and provides an audit trail of the reviewers' decisions, procedures and conclusions (Tranfield et al ., 2003, p. 209; Amer, 2023a, b).…”
Section: Theoretical Background Of Systematic Literature Review – Prismamentioning
confidence: 98%
“…It utilizes the Meta-Analysis approach, which employs a more transparent, scientific and replicable process. In other words, it is a detailed technology that aims to minimize bias through exhaustive literature searches and provides an audit trail of the reviewers' decisions, procedures and conclusions (Tranfield et al ., 2003, p. 209; Amer, 2023a, b).…”
Section: Theoretical Background Of Systematic Literature Review – Prismamentioning
confidence: 98%
“…Indian investors prioritize ESG factors that influence their investing decisions (Sood et al, 2023). Halal standard implementation in the Palestinian food sector is a major driver of its financial and stock market performance (Amer, 2023). Review work conducted on existing literature indicated diverse opinions on the kind of relationship recency, familiarity, confirmation, and overconfidence bias shared with financial decision-making.…”
Section: Literature Review Theoretical Framework and Hypotheses Devel...mentioning
confidence: 99%
“…The HSC refers to the flow of products from origin to consumption in which halal and toyyib conditions are taken into account along the supply chain (Omar and Jaafar, 2011). HSCM is responsible for maintaining the halal status throughout the supply chain by ensuring the integrity of halal through certifications (Amer, 2023). To maintain halal integrity up to the point of consumption, there are numerous uncertainties present.…”
Section: Halal Supply Chain and Risk Managementmentioning
confidence: 99%